Bio-hythane production from residual biomass of Chlorella sp. biomass through a two-stage anaerobic digestion. (4th February 2019) - Lunprom, Siriporn; Phanduang, Orawan; Salakkam, Apilak; Liao, Qiang; Imai, Tsuyoshi; Reungsang, Alissara
Abstract: Residual Chlorella sp. biomass obtained after anaerobic solid-state fermentation was used to produce bio-hythane. The residual biomass was pretreated using acid, thermal, and acid-thermal methods before their respective hydrolysates were used in dark fermentation followed by the methanogenesis of anaerobic digestion to produce hydrogen and methane, respectively. Pretreatment of the residual biomass using acid and thermal methods did not significantly increase reducing sugar production. However, a maximum reducing sugar content of 28.9 mg-reducing-sugar·g-biomass −1 was attained using an acid-thermal method, resulting in the highest hydrogen and methane yields of 12.5 and 81 mL·g-volatile-solid −1, respectively. This was equivalent to the total energy yield of 3.03 kJ·g-VS −1 or 4.6% energy recovery, based on the heating value of the residual biomass. Graphical abstract: Highlights: Residual Chlorella sp. biomass is a promising feedstock for bio-hythane production. Acid-thermal pretreatment gave the highest sugar yield among the methods tested. The highest H2 and CH4 yields were obtained from acid-thermal pretreated biomass. Bio-hythane containing 13.4% H2 was produced from acid-thermal pretreated biomass. Total energy of 3.03 kJ/g-VS was attained from acid-thermal pretreated biomass.